Sports branding as an object of scientific analysis based on the study of publications in the international scientometric database Scopus - Svitlana Stadnyk; Daria Okun; Anastasia Bondar; Natalia Sereda (Слобожанський науково-спортивний вісник, 2023)
Background and Study Aim: Sports branding is a systematic process of communication with a mass audience, aimed at creating a special sports culture: understanding the need to maintain a healthy lifestyle; maintaining interest in sports activities; formation of a positive image of the country through large-scale events, etc. Branding technologies are currently actively used not only by sports clubs, individual athletes, public authorities, but also by non-profit physical culture and sports organizations. Thus, this study was aimed at systematizing modern scientific ideas about sports branding. The purpose is a bibliometric analysis of sports branding research based on the study of publications in the international scientometric database Scopus.